SIMULATION BASED ANALYSIS ON THE EFFECTS OF ORIENTATION ON ENERGY PERFORMANCE OF RESIDENTIAL BUILDINGS IN GHANA (Journal of Science and Technology, 2016)
Since the energy crisis in 2007, energy performance of buildings is gradually becoming an issue in Ghana. The authors of this paper used simulation as a tool to analyse three conventional resi- dential building types, in order to see the effects of orientation on energy performance, specifi- cally on cooling loads. The three building types; a single storey square block, a single storey rec- tangular block and a two storey square block with different thermal properties were modelled and simulated. Alternate north angles were used and results compared for the best orientation resulting in minimum cooling loads in the climatic context of Kumasi, Ghana. The results on the rectangular building indicated the best orientation as being north and south. No particular ori- entation could be recommended for the single and two storey building (with square plans) and this showed that the influence of other factors such as windows, configuration and function of spaces, and building mass directly affected cooling loads and eventually orientation.